Multicriteria methodology for decoupling point placement under production postponement strategy (2016)
The accelerated growth of global markets and the increased bargaining power of customers, has generated a highly competitive environment with a lot of risks for manufacturing companies. In response, the literature has shown mass customization and, in particular way, the postponement strategy as new paradigms of production that allows offering simultaneously high levels of flexibility and efficiency to consumers. Regarding this issue, the decoupling point location is positioned as the most important decision in the implementation of postponement. Starting from the importance of this topic and from a review of the state of the art, it was detected the need to develop a methodology to locate the decoupling point, by integrating qualitative and quantitative criteria and that additionally allows the participation of panel of experts. Thereby, this thesis shows the development of a new multi-criteria methodology; which consists of 7 steps that allow locating the decoupling point, in a production system, according to the needs of the system and relying on the experience and knowledge of experts. Additionally, in order to validate the performance of the methodology in real cases, two study cases developed in the companies Herragro S.A. and Muebles Marco Gomez, are presented